Social workers perceptions on unionisation and collective bargaining : an exploratory study of the central region of the Eastern Cape - Dyakala, Tumeka (Rhodes University, Faculty of Humanities, Department of Social Work, 2000)
This study explores primarily the views of social workers in the Central region of the Eastern Cape on unionisation and collective bargaining, and at a secondary level the views of their employers and of the trade unions organising social workers, regarding social workers' involvement and non-involvement in these processes. It examines the paradox of compatibility of professionalism and unionism. There are two schools of thought regarding compatibility of professionalism and unionisation one views these concepts as antagonistic whilst the other views these concepts as complementary. Some social workers have been reluctant to participate in trade unions in the past until recently. Reasons advanced for their recent accelerated involvement in trade unions are explored in this study. Social workers views on the Labour Relations Act 66 of 1995 as the source of the legal framework, within which trade unions and employers interact, through the process of collective bargaining are explored. Proposed alternative mechanisms to these processes as perceived by social workers are closely examined. Semi-structured, self administered questionnaires were distributed to social workers whilst semi-structured interviews were conducted with employer representatives and trade union officials. This helped the researcher to have a broader view of the situation. Findings point to a scenario of disunity of both employers and employees in the social work profession. The study is a pioneering effort in the Central region and sets a way forward for further exploration of this subject. It is hoped that this study will make a worthwhile contribution to the social work profession's industrial relations field
Keywords: Social workers -- South Africa -- Eastern Cape -- Attitudes; Labor unions -- South Africa; Collective bargaining -- South Africa